A transmission electron microscopy study of microscopic causes for localized-corrosion morphology variations in the AA7055 Al alloy. Issue 10 (October 2018) - Yang, X.B.; Chen, J.H.; Zhang, G.H.; Huang, L.P.; Fan, T.W.; Ding, Y.; Yu, X.W.
Graphical abstract: Abstract: By Using (scanning) transmission electron microscopy, localized-corrosion morphology variations of the AA7055 AlZn(Cu)Mg alloy with different thermal processes and their underlying microscopic causes were investigated systematically. Our study shows that the corrosion resistance of the nanoscale precipitates varies with their structure type and Cu-content. Just like the Al-matrix, the early-stage precipitates are corrosion resistant, as compared with the ηp /η-precipitates without high Cu-content. With a high Cu-content, however, the η-precipitates become most corrosion resistant among all phases involved. Hence, tailoring the precipitate microstructure and chemistry though thermal processes may change the overall corrosion morphology and improve corrosion resistance property of the alloy.